Effects of infliximab on oxidative stress and inflammation of H9c2 cells induced by H2O2: Effect of infliximab in myocardial infarction - Yang, Tan; Hu, Shao Lian; Li, Lei; Wang, Yang; Jiang, Tao (Cellular and Molecular Biology, 2023)
This study investigated the effects of infliximab (INF) on oxidative stress and inflammation in H9c2 cardiomyocytes, aiming to address the damage caused by myocardial infarction (MI). H9c2 cells were divided into three groups: control, H2O2 treatment, and H2O2+INF. Cell viability was assessed using the Cell Counting Kit-8 (CCK-8) assay. Protein expression of SOD1, SOD2, TNF-α, and IL-1β was examined through Western blot, while mRNA expression was analyzed via polymerase chain reaction (PCR). Reactive oxygen species (ROS) levels were measured, and IL-1β immunofluorescence was utilized to observe inflammation. The expression of IκB-α and IκKα was evaluated to investigate the mechanism of action. INF significantly improved H9c2 cell viability and reduced LDH and MDA levels in the supernatant. Moreover, INF enhanced the expression of SOD1 and SOD2, reducing ROS production. In comparison to the H2O2 group, TNF-α and IL-1β expression markedly decreased in the H2O2+INF group. Additionally, the fluorescence intensity of IL-1β immunofluorescence was higher in the H2O2+INF group. INF treatment decreased TNF-α and IL-1β expression and reduced IL-1β fluorescence intensity. Furthermore, INF increased IκB-α expression and decreased IκKα expression, suggesting inhibition of the nuclear factor-κB (NF-κB) pathway. In summary, INF effectively suppressed H2O2-induced oxidative stress and inflammation in H9c2 cells by targeting the NF-κB pathway.